Clinical bioethics integration, sustainability, and accountability: the Hub and Spokes Strategy. Issue 5 (29th April 2005) - MacRae, S; Chidwick, P; Berry, S; Secker, B; Hébert, P; Shaul, R Zlotnik; Faith, K; Singer, P A
Abstract : The "lone" clinical bioethicist working in a large, multisite hospital faces considerable challenges. While attempting to build ethics capacity and sustain a demanding range of responsibilities, he or she must also achieve an acceptable level of integration, sustainability, and accountability within a complex organisational structure. In an effort to address such inherent demands and to create a platform towards better evaluation and effectiveness, the Clinical Ethics Group at the Joint Centre for Bioethics at the University of Toronto is implementing the Hub and Spokes Strategy at seven hospitals. The goal of the Hub and Spokes Strategy is to foster an ethical climate and strengthen ethics capacity broadly throughout healthcare settings as well as create models in clinical bioethics that are excellent and effective.